EFEKTIFITAS PEMBELAJARAN DENGAN EKSPERIMEN TAK TERINTEGRASI DIDAHULUI PEMBERIAN PETA KONSEP TERHADAP PRESTASI BELAJAR SISWA SMA BATIK 2 SURAKARTA - OETOMO, DWI (P Biologi FKIP UNS Surakarta, 2015)
The purpose of this research is to compare the un-integrated experimental and lecture teaching methods. In the un-integrated experimental teaching method, the students are given a concept chartfirst. The subject matter of this research is the movement on plants; This research used experimental method with randomized control-group only design. The populations are the second grade students of SMU Batik 2 Surakarta, year 2013/2014 The sample is 86 students that taken using cluster random sampling technique. The first data are taken from the value of once grade students of an odd semester. They are used to test the early ability of students. The second data are gotten from post test. Data are analyzed using t-test. The conclusion of this research is that the teaching using un-integrated experimental methods is more effective to increase the achievement of students than conventional method.. Keywords: un-integrated experimental method, convention method, student achievement